Guardian of the Genome: An Alternative RAG/Transib Co-Evolution Hypothesis for the Origin of V(D)J Recombination - Yakovenko, Iryna; Agronin, Jacob; Smith, L. Courtney; Oren, Matan (Frontiers in Immunology, 2021)
The appearance of adaptive immunity in jawed vertebrates is termed the immunological ‘Big Bang’ because of the short evolutionary time over which it developed. Underlying it is the recombination activating gene (RAG)-based V(D)J recombination system, which initiates the sequence diversification of the immunoglobulins and lymphocyte antigen receptors. It was convincingly argued that the RAG1/2 genes originated from a transposon. The current dogma postulates that the V(D)J system was established by at least two genomic insertions of this transposon, leading to a gene that was split into V(D)J segments in parallel with transposon domestication as the RAG recombinase. Here, based on the recently accumulated data, we propose an alternative evolutionary hypothesis suggesting that the RAG1/2 transposase was first domesticated to serve as a guardian of the genome against invasions of other transposons, and eliminated all but one Transib invader with asymmetric terminal inverted repeats, which survived because of the evolutionary advantage it provided. This hypothesis offers an alternative understanding of the origin and early evolution of the V(D)J system.